# calc

posted by .

eliminate parameter t when
x= ln(sqrt(1+t^2)+t) and y = sqrt(t^2+1
so to produce an equation y=f(x).

## Similar Questions

1. ### Inequality

When I solve the inquality 2x^2 - 6 < 0, I get x < + or - sqrt(3) So how do I write the solution?

3. ### math,algebra,help

Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces …
4. ### Math

How do you find a square root of a number that's not a perfect square?
5. ### Mathematics

sqrt 6 * sqrt 8 also sqrt 7 * sqrt 5 6.92820323 and 5.916079783 So you can see the steps — sqrt 6 * sqrt 8 = sqrt 48 sqrt 7 * sqrt 5 = sqrt 35 I hope this helps a little more. Thanks for asking.

Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
7. ### calc ii

eliminate parameter t when x= ln(sqrt(1+t^2)+t) and y = sqrt(t^2+1)
8. ### calc ii

eliminate parameter t when x= ln(sqrt(1+t^2)+t) and y = sqrt(t^2+1 so to produce an equation y=f(x).
9. ### calc

eliminate parameter t when x= ln(sqrt(1+t^2)+t) and y = sqrt(t^2+1 so to produce an equation y=f(x).
10. ### Algebra

Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work. sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2) x*sqrt 7x-49*x ^^^ would this be my final answer?

More Similar Questions